2002
DOI: 10.1136/vr.150.8.245
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of systemic inflammatory response syndrome criteria as an index for prognosis judgement

Abstract: Usefulness of systemic 30inflammatory response 25syndrome criteria as an 20index for prognosis ia judgement 2 10-5-Veterinary Record (2002)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 12 publications
3
67
0
Order By: Relevance
“…24,g In dogs with CPV infection, there was no predictive value associated with fulfillment of the SIRS criteria in relationship to duration of hospitalization. Regardless of whether the criteria suggested by Hauptman et al 21 or Okano et al 23 were applied to the data collected in the present study, there was no relationship between fulfillment of the SIRS criteria and duration of antiemetic administration or duration of hospitalization.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…24,g In dogs with CPV infection, there was no predictive value associated with fulfillment of the SIRS criteria in relationship to duration of hospitalization. Regardless of whether the criteria suggested by Hauptman et al 21 or Okano et al 23 were applied to the data collected in the present study, there was no relationship between fulfillment of the SIRS criteria and duration of antiemetic administration or duration of hospitalization.…”
Section: Discussionmentioning
confidence: 49%
“…20 Such SIRS criteria have also been proposed for dogs by several authors. [21][22][23] However, the specificity of these diagnostic criteria for sepsis in dogs is low, as reported by Hauptman et al 21 Okano et al 23 selected much more stringent criteria that limited the sensitivity of the criteria. After initial analysis of the data collected in the present study, the less stringent published SIRS criteria (as suggested by Hauptman et al 21 ) were applied to all dogs on day 1 and identified 65 of 77 dogs as having SIRS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Dogs presented to the medical Emergency and Critical Care Service with SIRS, and that required Intensive Care Unit (ICU) hospitalization afterward, were prospectively included in this observational clinical study. The diagnosis of SIRS was based upon fulfillment of ≥2 of the established SIRS criteria as described in a previous publication:36 Hypo‐or hyper‐thermia (<37.8°C or >39.7°C)Tachycardia (>160 heart rate/min)Tachypnea (>40 breaths/min)PCO 2 (≤32 mmHg)Leukopenia or leukocytosis (<4.0 × 10 9 /L or >12.0 × 10 9 /L)Immature (band) neutrophils >10% …”
Section: Methodsmentioning
confidence: 99%
“…The SIRS classification was introduced to describe the clinical response to systemic inflammation and has been applied to patients with inflammatory disease 35, 36, 37. The SIRS classification is based on basic clinical and laboratory parameters.…”
mentioning
confidence: 99%